The Effect of Price and Product Quality on Purchase Decisions Among Economic Education Students - Puji, Siti Fatimah; Kadori Haidar; Ilham Abu; Sutrisno (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2024)
This type of research uses quantitative research with a descriptive approach. The sample used was 60 respondents from students of the 2020 and 2021 generations of Economic Education. Data analysis used is multiple linear regression analysis. The results of this study showed the results of the T test for the price variable with a significance value of 0.003 < 0.05 and the calculated t count of 3.139 > t table = 2.002. Then it can be concluded that the price partially has a significant effect on the purchase decision. T test results for product quality variables with a significance value of 0.000 < 0.05 and the value of t count = 4.502 > t table = 2.002. It can be concluded that the quality of the product is partially a significant influence on purchasing decisions. F test calculation results obtained significance value 0.001 < 0.05 and the value of f count = 47.934 > f table = 3.156. Then it can be concluded that the price and quality of the product simultaneously have a significant effect on the purchase decision. Test results coefficient R Square (R2) of 0.627, it can be concluded that the influence of price and product quality on purchasing decisions is equal to 62.7%. While the remaining 37.3% were influenced by other variables that were not studied in this study.